Damped Algorithms for the Split Fixed Point and Equilibrium Problems. (25th September 2013) - Zhu, Li-Jun; Ren, Minglun
Abstract : The main purpose of this paper is to study the split fixed point and equilibrium problems which includes fixed point problems, equilibrium problems, and variational inequality problems as special cases. A damped algorithm is presented for solving this split common problem. Strong convergence analysis is shown.